Manager's guide to virtual teams - Fisher, Kimball; Fisher, Mareen Duncan (New York : McGraw-Hill, 2011)
A hands-on guide for managing people and projects working from home, on the road, or in client sites; covers every aspect of virtual management--motivation, building teams, meeting deadlines, file sharing, teleconferencing, email, coaching, and videoconferencing.
What is a virtual team? -- Managing space, time, and culture -- The seven competencies of effective virtual team leaders -- What virtual team employees need from their manager -- Bridging culture differences -- Starting up (or refocusing) a virtual team -- Building trust from a distance -- Using telephonic collaboration technologies -- Using videoconferencing and internet-based collaboration tools -- Improving the business IQ of team members -- Teaching finance fundamentals to virtual teams -- Improving communication and feedback skills -- Creative problem solving for virtual teams -- Managing performance from a distance -- Effective decision making over distance -- Virtual team building -- Maintaining a balanced personal and work life.
Includes index.
Keywords: Teams in the workplace; Personnel management; Telecommuting; Virtual work teams -- Management